2018
DOI: 10.1002/ente.201700843
|View full text |Cite
|
Sign up to set email alerts
|

NiMo‐Ceria‐Zirconia Catalyst for Inert‐Substrate‐Supported Tubular Solid Oxide Fuel Cells Running on Model Gasoline

Abstract: A NiMo‐ceria‐zirconia catalyst was developed for an inert‐substrate‐supported tubular single cell running on isooctane fuel. The tubular single cell consisted of an inert porous yttira‐stabilized zirconia (YSZ) supporter, Ni‐Ce0.8Sm0.2O1.9 (Ni‐SDC) anode, YSZ/SDC bilayer electrolyte and La0.6Sr0.4Co0.2Fe0.8O3−δ (LSCF) cathode. The NiMo‐ceria‐zirconia catalyst was packed in the tubular channel of the single cell as a reforming unit. With application of the catalyst in the tubular cell, the mixture of isooctane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Our previous studies demonstrated that the NiMo/CZ catalyst possesses an excellent performance for CPOX of isooctane at a temperature higher than 750 °C. [ 13–15 ] In this work, CPOX of isooctane was carried out at a lower temperature of 700 °C and a high WHSV of 15 h −1 . The catalytic activity and stability results for CPOX of isooctane over NiMo/CZ and NiMoRu/CZ catalysts are shown in Figure 2 in terms of isooctane conversion and CO and H 2 yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies demonstrated that the NiMo/CZ catalyst possesses an excellent performance for CPOX of isooctane at a temperature higher than 750 °C. [ 13–15 ] In this work, CPOX of isooctane was carried out at a lower temperature of 700 °C and a high WHSV of 15 h −1 . The catalytic activity and stability results for CPOX of isooctane over NiMo/CZ and NiMoRu/CZ catalysts are shown in Figure 2 in terms of isooctane conversion and CO and H 2 yields.…”
Section: Resultsmentioning
confidence: 99%
“…Ni‐based bimetallic nanoparticles doped with Mo and supported over cerium–zirconium oxide (CZ) were used in our previous studies as an internal reforming layer over a conventional Ni–YSZ anode to form a bilayer anode structure. [ 13–15 ] The nickel–molybdenum (NiMo)/CZ catalyst showed excellent catalytic activity and stability at a temperature higher than 750 °C for liquid fuel reforming with improved coking resistance compared with the Ni/CZ. However, low reforming performance is expected on the catalyst layer when the experiment is conducted at the lower SOFC operating temperatures (<750 °C).…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical performance of the button cell was measured using a custom home‐made fuel cell test system, as we used in our previous publications. [ 9,10 ] The test system consisted of mass flow controllers (Brooks 8580E), a DC electric load (BK precision 8500), and an Autolab electrochemical workstation (Metrohm Autolab M101).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the system simplicity offered by the internal reforming SOFC, various researches have been conducted in this area in the past two decades. [ 9–11 ] To efficiently operate SOFC under the direct feeding condition of ethanol, an anode that possesses a high electronic and ionic conductivity, a high reforming activity toward ethanol reforming and high coking resistance are needed. [ 12 ] Nickel–yttria–stabilized zirconia (Ni–YSZ) cermet is the conventional anode material for H 2 SOFC due to its excellent electronic–ionic conductivity and phase stability under reducing conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation